Double-eutectic electrolyte of low-temperature zinc ion battery as well as preparation method and application of double-eutectic electrolyte
Through the combination of hydrated eutectic electrolyte of zinc salt, acetamide and water and dimethyl sulfoxide, the hydrogen bond network is optimized, and the side reaction and corrosion problems of zinc ion batteries are solved at low temperatures, achieving uniform deposition of zinc ions and stable cycle at high current density extend battery life.
Patent Information
- Application Number
- CN202411511762.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Zinc ion batteries fail at low temperatures due to side reactions and freezing problems caused by water. The high viscosity and low ionic conductivity of anhydrous eutectic electrolyte hinder zinc ions migration. Hydrated eutectic electrolyte causes corrosion problems and cannot adapt to high Charge and discharge test of current density.
Using hydrated eutectic electrolytes of zinc salt, acetamide and water, and by adding dimethyl sulfoxide as hydrogen bond acceptor, the hydrogen bond network is optimized to form a low-temperature zinc ion battery dual eutectic electrolyte, promoting the uniformity of zinc ions Deposition and ion migration reduce corrosion risk.
The stable circulation of zinc ion batteries at low temperatures is achieved, the freezing point is reduced, the normal operation is ensured at -20℃, and the stable charging and discharge cycle is achieved under high current density, extending the service life of the battery.
Smart Images

Figure CN119181878A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of zinc ion batteries, and in particular relates to a low-temperature zinc ion battery double eutectic electrolyte and a preparation method and application thereof. Background Art
[0002] With the continuous progress of society, the development of the energy field has gradually come into people's view. In order to cope with the energy crisis and climate problems, clean renewable energy came into being. However, the intermittent and volatile supply of this type of clean energy limits its further application. In order to achieve a stable energy supply, large-scale energy storage devices are urgently needed to act as a "bridge" for energy storage. At present, lithium-ion batteries with high energy density and long cycle life are the mainstream of commercial applications, but lithium-ion batteries have problems such as high manufacturing cost, poor safety, and lack of lithium metal, and cannot be used in large-scale energy storage. Zinc-ion batteries have become one of the most promising energy storage systems at present because of their outstanding advantages of high theoretical specific capacity, high zinc abundance, and high intrinsic safety.
[0003] Although zinc-ion batteries have outstanding advantages in large-scale energy storage, challenges such as dendrite growth, corrosion passivation, and hydrogen evolution reaction (HER) during the cycle process hinder zinc-ion batteries from moving from the laboratory to commercial applications. As a part of the battery, the electrolyte plays a vital role in the electrochemical process. For conventional aqueous electrolytes, the inner and outer solvation shells of zinc ions are composed of active water molecules, which are prone to water-induced side reactions such as corrosion and hydrogen evolution reaction during the desolvation of zinc ions. At the same time, water molecules are prone to freezing below zero degrees, resulting in battery failure at low temperatures. Eutectic electrolytes have become potential electrolytes for zinc-ion batteries due to their excellent properties such as high safety, wide temperature window, and wide electrochemical window. However, anhydrous eutectic electrolytes composed only of zinc salts and ligands have the disadvantages of high viscosity and low ionic conductivity, which hinder the migration of zinc ions, resulting in slow zinc deposition and severe polarization, and cannot adapt to charge and discharge tests at high current density. Although the hydrated eutectic electrolyte improves the hysteresis problem of ion migration, it reintroduces the series corrosion problem, limiting the further application of the electrolyte.
[0004] Therefore, developing a eutectic electrolyte that can both promote ion migration and reduce corrosion is of great significance to the development of zinc-ion batteries. Summary of the invention
[0005] In order to solve the above problems, the present invention proposes a low-temperature zinc ion battery double eutectic electrolyte and a preparation method and application thereof.
[0006] The present invention adopts the following technical solutions:
[0007] A method for preparing a low-temperature zinc ion battery double eutectic electrolyte comprises the following steps:
[0008] S1, mixing zinc salt, acetamide and water in proportion, heating and stirring, and mixing evenly to obtain a hydrated eutectic electrolyte; wherein the molar ratio of the zinc salt, acetamide and water is 1:(3-6):(2.5-26), and water serves as a hydrogen bond donor;
[0009] S2. Mix dimethyl sulfoxide and the hydrated eutectic electrolyte, heat and stir, and after mixing evenly, obtain a low-temperature zinc ion battery double eutectic electrolyte; wherein the molar ratio of the dimethyl sulfoxide to the water in step S1 is (2.5-26):2, and dimethyl sulfoxide serves as a hydrogen bond acceptor.
[0010] Preferably, the zinc salt in step S1 is one of zinc chloride, zinc perchlorate hexahydrate, zinc trifluoromethanesulfonate or zinc bistrifluoromethanesulfonyl imide.
[0011] Preferably, the concentration of zinc salt in the low-temperature zinc ion battery double eutectic electrolyte in step S2 is 1 to 5 mol / L.
[0012] Preferably, in step S1, the heating temperature is 70-80° C., the stirring speed is 300-400 rpm, and the mixing time is 2-3 h.
[0013] Preferably, in step S2, the heating temperature is 70-80° C., the stirring speed is 300-400 rpm, and the mixing time is 0.5-2 h.
[0014] A low-temperature zinc ion battery double eutectic electrolyte is prepared by adopting the preparation method of the low-temperature zinc ion battery double eutectic electrolyte.
[0015] An application of a low-temperature zinc ion battery double eutectic electrolyte, wherein the low-temperature zinc ion battery double eutectic electrolyte is applied as an electrolyte to a zinc ion battery.
[0016] Preferably, the zinc ion battery uses sodium vanadate as the positive electrode, a zinc sheet as the negative electrode, glass fiber as the separator, and a low-temperature zinc ion battery double eutectic electrolyte as the electrolyte.
[0017] Preferably, the negative electrode, separator, electrolyte, positive electrode, stainless steel sheet and shrapnel are sequentially packaged into the battery shell, the packaging pressure is 50-80 MPa, and the addition amount of the low-temperature zinc ion battery double eutectic electrolyte is 140-180 μL.
[0018] After adopting the above technical solution, the present invention has the following advantages compared with the background technology:
[0019] 1. The present invention synthesizes a low-temperature zinc ion battery double eutectic electrolyte based on different eutectic effects between zinc salts, acetamide, water and dimethyl sulfoxide. First, zinc ions will coordinate with acetamide through Lewis acid-base interactions, replacing part of the water molecules in the inner solvation shell, reducing the desolvation energy barrier during the deposition process, thereby promoting the uniform deposition of zinc ions. Secondly, by rationally optimizing the addition amount of polar water molecules, the ion migration kinetics are improved and the interfacial polarization of the cycle at high current density is reduced. Finally, in the outer solvation shell, the hydrogen bond acceptor dimethyl sulfoxide and the hydrogen bond donor water molecules will interact with each other through hydrogen bonds, breaking the continuous hydrogen bond network of water molecules and inhibiting hydrogen evolution and corrosion reactions. The electrolyte prepared based on the double eutectic effect, i.e., coordination and hydrogen bonding, can effectively improve the stability and corrosion resistance of the negative electrode.
[0020] 2. In the low-temperature zinc ion battery double eutectic electrolyte of the present invention, the double eutectic effect, namely the coordination effect and the hydrogen bond effect, is rationally utilized to adjust the solvation shell of the zinc ion, effectively balance the ionic conductivity of the eutectic electrolyte and the water-oxygen corrosion reaction, and overcome the shortcomings of the anhydrous eutectic electrolyte by optimizing the addition amount of high-polarity and low-viscosity water molecules, so that the battery can be at 5 mA / cm 2 Stable charge-discharge cycles were achieved at a high current density of 5 A / g.
[0021] 3. Based on the different eutectic effects in the zinc ion solvation shell, the present invention reduces the freezing point of the low-temperature zinc ion battery double eutectic electrolyte, so that it can operate normally at a low temperature of -20°C, and the low-temperature zinc ion battery double eutectic electrolyte is 0.5mA / cm 2 -0.5mAh / cm 2 Under the conditions of stable cycle for more than 8000 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The infrared spectra of the zinc ion battery electrolytes prepared in Comparative Examples 1 and 2 and Example 1 of the present invention are as follows;
[0023] Figure 2 The Raman spectra of the zinc ion battery electrolytes prepared in Comparative Examples 1 and 2 and Example 1 of the present invention are as follows;
[0024] Figure 3 The ionic conductivity and viscosity diagram of the zinc ion battery electrolyte prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;
[0025] Figure 4 A comparison chart of hydrogen production corresponding to different numbers of cycles of zinc ion battery electrolytes prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;
[0026] Figure 5XRD pattern of the zinc foil surface of the Zn||Zn symmetrical battery assembled with the zinc ion battery electrolyte prepared in Comparative Examples 1 and 2 and Example 1 of the present invention after 20 cycles;
[0027] Figure 6 SEM image of the zinc foil surface of the Zn||Zn symmetrical battery assembled with the zinc ion battery electrolyte prepared in Comparative Examples 1 and 2 and Example 1 of the present invention after 50 cycles;
[0028] Figure 7 DSC curves of the zinc ion battery electrolytes prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;
[0029] Figure 8 The Zn||Zn symmetric battery assembled by the zinc ion battery electrolyte prepared in Comparative Examples 1, 2 and Example 1 of the present invention is 1 mA / cm 2 Constant current charge and discharge curve diagram below;
[0030] Fig. 9 The Zn||Zn symmetric battery assembled with the zinc ion battery electrolyte prepared in Comparative Examples 1, 2 and Example 1 of the present invention has a high current density of 5 mA / cm 2 Constant current charge and discharge curve diagram below;
[0031] Fig.10 The cycle performance diagram of the Zn||Zn symmetrical battery assembled with the zinc ion battery electrolyte prepared in Comparative Example 2 and Example 1 of the present invention at -20°C;
[0032] Fig.11 The coulomb efficiency test diagram of the Zn||Cu asymmetric battery assembled with the zinc ion battery electrolyte prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;
[0033] Fig.12 The coulomb efficiency test diagram of the Zn||Cu asymmetric battery assembled with the zinc ion battery electrolyte prepared in Comparative Example 2 and Example 1 of the present invention at -20°C;
[0034] Fig.13 The constant current charge-discharge curve of the Zn||NVO full battery assembled with the zinc ion battery electrolyte prepared in Comparative Example 1 and Example 1 of the present invention at 5A / g;
[0035] Fig.14 The cycling performance diagram of the Zn||NVO full battery assembled with the zinc ion battery electrolyte prepared in Example 1 of the present invention at -20°C. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0037] See also Figures 1 to 14 .
[0038] Example 1
[0039] Zinc trifluoromethanesulfonate, acetamide and deionized water were mixed in a molar ratio of 1:3:24, heated and stirred at 80°C and 350 rpm for 2 hours to obtain a clear liquid, and then dimethyl sulfoxide was added in a molar ratio of deionized water and dimethyl sulfoxide of 24:2, and heated and stirred at 80°C and 350 rpm for 0.5 hour, and then cooled to room temperature to obtain a low-temperature zinc ion battery double eutectic electrolyte with a concentration of 1.3 mol / L.
[0040] Comparative Example 1
[0041] Weigh an appropriate amount of zinc trifluoromethanesulfonate and dissolve it in deionized water, and stir it at room temperature to prepare a 1.3 mol / L aqueous electrolyte for zinc ion batteries.
[0042] Comparative Example 2
[0043] Zinc trifluoromethanesulfonate, acetamide and deionized water were mixed in a molar ratio of 1:3:32, heated and stirred at 80°C for 2 hours to obtain a clear solution, which was then cooled to room temperature to obtain a zinc ion battery hydrated eutectic electrolyte with a concentration of 1.3 mol / L.
[0044] Test Example 1
[0045] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 and pure acetamide were subjected to infrared spectroscopy testing. The infrared spectra obtained are shown in FIG. Figure 1 shown.
[0046] Depend on Figure 1 It can be seen that the C=O stretching region of acetamide changes significantly from 1672 cm -2 The band redshifted to 1658cm -2 , which indicates that Zn 2+ The formation of a coordination bond with C=O weakens the original C=O double bond effect, and at the same time proves that the addition of acetamide changes the solvation structure around the zinc ion.
[0047] Test Example 2
[0048] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1, as well as pure zinc trifluoromethanesulfonate, acetamide and dimethyl sulfoxide were subjected to Raman spectroscopy test. The obtained Raman spectra are shown in FIG. Figure 2 shown.
[0049] Depend on Figure 2 It can be seen that with the introduction of acetamide, the original 1034 cm -1 The S=O vibration peak at the position of the blue shifted, indicating that Zn appeared in the solvated clusters of Comparative Example 2. 2+ With OTf - The addition of dimethyl sulfoxide causes the S=O in Example 2 to undergo a further blue shift. Compared with pure dimethyl sulfoxide solvent, the S=O peak in Example 1 undergoes a red shift, while the -CH3 symmetric and asymmetric stretching vibration peaks undergo a blue shift, which indicates that after the addition of dimethyl sulfoxide in Example 1, the S=O bond and the -CH3 bond are stretched and compressed, respectively, proving that hydrogen bonds are formed between dimethyl sulfoxide and water molecules.
[0050] Test Example 3
[0051] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 were assembled into stainless steel||stainless steel batteries, and the ionic conductivity was tested using an electrochemical workstation, and the viscosity of the electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 was measured using a rotational rheometer. The results are as follows: Figure 3 shown.
[0052] Depend on Figure 3 It can be seen that after the molar ratio between the components is optimized, the ionic conductivity and viscosity in Example 1 are at the same order of magnitude as those in Comparative Example 1 and Comparative Example 2, and the test result of Example 1 is close to the measured value of Comparative Example 1, indicating that the introduction of low-viscosity water molecules enhances the ion transport kinetics in the eutectic electrolyte.
[0053] Test Example 4
[0054] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 were subjected to a hydrogen evolution test.
[0055] First, the zinc foil was cut into a 1 cm × 1 cm square shape, and the cut zinc foil was used as the working electrode and the counter electrode, the Ag / AgCl electrode was used as the reference electrode, and the comparative example 1, comparative example 2 and embodiment 1 were used as the electrolyte to assemble a three-electrode electrolytic cell. The three-electrode electrolytic cell was subjected to a ventilation test to remove oxygen and other interfering gases in the electrolytic cell. Then, at 5 mA / cm 2 The cycle test was carried out at a current density of 1.5 200 ℃ and the amount of hydrogen produced in different cycle times was monitored by gas chromatography (Agilent 7890B). The test results are shown in Figure 4 shown.
[0056] Depend on Figure 4It can be seen that the hydrogen production rate of Comparative Example 1 is significantly higher than that of Comparative Example 2 and Example 1, and as the number of cycles increases, the hydrogen production rate remains at a high level, which indicates that a strong water-induced side reaction occurs in the cycle process. In contrast, the hydrogen production rate of Example 1 is significantly lower than that of Comparative Example 2. After a short period of hydrogen evolution, the hydrogen production concentration of Example 1 gradually stabilizes. This proves that the addition of dimethyl sulfoxide successfully destroys the hydrogen bonds between water molecules, inhibits the activity of water molecules, and thus effectively inhibits the hydrogen evolution reaction.
[0057] Test Example 5
[0058] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 were assembled into Zn||Zn symmetrical cells. 2 The XRD comparison of the zinc foil surface after 20 cycles at a current density of Figure 5 shown.
[0059] Depend on Figure 5 It can be seen that Zn appeared on the surface of the zinc negative electrode after cycling in Comparative Example 1. x OTf y (OH) 2x-y The peak of the by-product nH2O was also observed in Comparative Example 2, which indicates that in Comparative Example 2, Zn 2+ Active water molecules in the solvation shell still cause corrosion. In Example 1, only the signal of zinc foil was detected, and almost no peaks related to by-products were observed, which shows that Zn 2+ The reconstruction of the hydrogen-bonding network of water molecules in the solvation shell effectively suppresses the generation of by-products during the cycle.
[0060] Test Example 6
[0061] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 were assembled into Zn||Zn symmetrical cells. 2 The SEM image of the zinc foil surface after 50 cycles of electroplating / stripping at a current density of Figure 6 shown.
[0062] Depend on Figure 6It can be obtained that the surface of the zinc negative electrode cycled using Comparative Example 1 presents a randomly oriented zinc distribution, and the zinc deposition is very loose and has holes. This irregular stacking will promote the growth of dendritic dendrites, and the shedding of dead zinc will lead to loose zinc deposition, resulting in battery short circuit failure. In Comparative Example 2, the zinc surface after cycling presents a dense flaky zinc stack, but the zinc deposition orientation is still disordered, so that the irregular stacking of flaky zinc will cause zinc to continue to deposit along favorable sites to form dendrites. The zinc surface after cycling using the electrolyte of Example 1 presents a uniform and dense morphology, which indicates that the regulation of the zinc ion solvation structure in Example 1 effectively promotes the uniform deposition of zinc and inhibits the growth of dendrites.
[0063] Test Example 7
[0064] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 were subjected to DSC test. The results are as follows: Figure 7 shown.
[0065] Depend on Figure 7 It can be obtained that the freezing point of the electrolyte in comparative example 1 is -11.26°C, the freezing point corresponding to the electrolyte in comparative example 2 is -20.02°C, and the freezing point of the electrolyte in embodiment 1 is -30.16°C. The test results show that the electrolyte in comparative example 1 will freeze at a low temperature of -20°C and cannot be tested at -20°C. Thanks to the combined effect of the coordination bond and hydrogen bond in the electrolyte in embodiment 1, the freezing point of the electrolyte in embodiment 1 is significantly reduced, which is beneficial to the charge and discharge test of the battery at low temperature.
[0066] Test Case 8
[0067] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 were assembled into Zn||Zn symmetrical cells. 2 and 5mA / cm 2 The cycle performance test was carried out at a current density of Figure 8 and Fig. 9 shown.
[0068] First, use a cutting machine to cut the zinc foil into discs with a diameter of 12 mm, put the cut zinc sheet into a prepared phosphoric acid solution with a concentration of 0.1 mol / L to remove the zinc oxide layer on the surface, take out the zinc sheet after 30 seconds, and use ethanol and deionized water to ultrasonically clean it three times alternately, each time for two minutes, vacuum dry it at 60°C for 2 hours, and cool it to obtain a treated zinc sheet negative electrode. Then, according to the assembly sequence of CR2032 type negative electrode shell, zinc sheet (thickness of 80μm), glass fiber diaphragm (thickness of 675μm), electrolyte, zinc sheet, stainless steel sheet, shrapnel, and CR2032 type positive electrode shell, a Zn||Zn symmetrical battery is assembled in sequence. Among them, the packaging pressure of the battery is 50MPa, and the electrolyte used is the electrolyte prepared in Comparative Example 1, Comparative Example 2 and Example 1 (the amount of addition is 180μL). Finally, at 1mA / cm 2 Current density, 1mAh / cm 2 Area capacity and 5mA / cm 2 The current density is 5 mAh / cm 2 The Zn||Zn symmetrical battery was cycle tested using the Xinwei battery charge and discharge test system at an area capacity of .
[0069] Depend on Figure 8 and Fig. 9 It can be seen that the battery assembled using Comparative Example 1 and Comparative Example 2 has an output current of 1 mA / cm 2 and 5mA / cm 2 When cycling at a current density of 1 mA / cm2, the charge-discharge curve fluctuates or even short-circuits in a short period of time. In contrast, the Zn||Zn battery assembled using Example 1 has better cycle stability. 2 Current density, 1mAh / cm 2 The area capacity can be stably cycled for nearly 5900 hours at 5mA / cm 2 The current density is 5 mAh / cm 2 This indicates that the electrolyte in Example 1 has a good effect of stabilizing the zinc negative electrode and significantly prolongs the cycle life of the battery.
[0070] Test Example 9
[0071] The electrolytes prepared in Comparative Example 2 and Example 1 were assembled into Zn||Zn symmetrical batteries, and the cycle performance test was carried out at a low temperature of -20°C. The test results are as follows: Fig.10 shown.
[0072] First, the zinc foil was cut into discs with a diameter of 12 mm using a cutting machine, and the cut zinc sheet was placed in a prepared phosphoric acid solution with a concentration of 0.1 mol / L to remove the zinc oxide layer on the surface. After 30 seconds, the zinc sheet was taken out and ultrasonically cleaned three times with ethanol and deionized water alternately for two minutes each time, vacuum dried at 60°C for 2 hours, and cooled to obtain a treated zinc sheet negative electrode. Then, a Zn||Zn symmetrical battery was assembled in the order of CR2032 type negative electrode shell, zinc sheet (thickness of 80 μm), glass fiber diaphragm (thickness of 675 μm), electrolyte, zinc sheet, stainless steel sheet, shrapnel, and CR2032 type positive electrode shell. Among them, the packaging pressure of the battery is 50 MPa, and the electrolyte used is the electrolyte prepared in Comparative Example 2 and Example 1 (the amount of drop is 180 μL). Finally, the assembled battery was placed in a low temperature test box (DM-50) at a low temperature of -20°C and 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 The Zn||Zn symmetrical battery was cycle tested using the Xinwei battery charge and discharge test system under the condition of area capacity.
[0073] Depend on Fig.10 It can be seen that the battery assembled using Comparative Example 2 can stably cycle for more than 2000 hours at -20°C, and the Zn||Zn symmetrical battery assembled using the electrolyte of Example 1 can stably cycle for more than 2000 hours at -20°C and 0.5 mA / cm 2 -0.5mAh / cm 2 The electrolyte of Example 1 has a cycle life of more than 8000 hours under the condition of , and the voltage curve during the cycle shows a stable voltage polarization. This shows that the electrolyte of Example 1 has good low temperature tolerance and a long cycle life at low temperatures.
[0074] Test Example 10
[0075] The electrolytes prepared in Comparative Example 1, Comparative Example 2 and Example 1 were assembled into Zn||Cu asymmetric cells and used for coulombic efficiency tests at room temperature and low temperature. The results are as follows: Fig.11 and Fig.12 shown.
[0076] First, use a cutting machine to cut the zinc foil into discs with a diameter of 12 mm, put the cut zinc sheet into a prepared phosphoric acid solution with a concentration of 0.1 mol / L to remove the zinc oxide layer on the surface, take out the zinc sheet after 30 seconds, and use ethanol and deionized water to ultrasonically clean it three times alternately, each time for two minutes, vacuum dry it at 60°C for 2 hours, and cool it to obtain a treated zinc sheet negative electrode. Then, assemble the Zn||Cu battery in the order of CR2032 type negative electrode shell, zinc sheet (thickness of 80μm), glass fiber diaphragm (thickness of 675μm), electrolyte, copper sheet, stainless steel sheet, shrapnel, and CR2032 type positive electrode shell. Among them, the packaging pressure of the battery is 50MPa, and the electrolyte used for room temperature testing is the electrolyte prepared in Comparative Example 1, Comparative Example 2 and Example 1 (the amount of addition is 180μL), with a current of 1mA / cm 2 The current density and 0.5 mAh / cm 2 The surface capacity of the battery was tested for coulombic efficiency using the Xinwei charge and discharge test system. The electrolyte used in the low-temperature test was the electrolyte prepared in Comparative Example 2 and Example 1 (the amount of addition was 180 μL), and the battery was tested in a low-temperature test box (DM-50) at 0.5 mA / cm 2 The current density is 0.25 mAh / cm 2 The surface capacity of the battery is tested for coulombic efficiency using the Xinwei charge and discharge test system.
[0077] Depend on Fig.11 and Fig.12 It can be obtained that at room temperature, after 70 cycles in the electrolyte of Comparative Example 1, the coulombic efficiency fluctuates or even drops sharply due to irreversible side reactions and dendrite growth. The coulombic efficiency of the electrolyte of Comparative Example 2 fluctuates around 540 cycles, which shows that the presence of adverse corrosion reactions in the electrolyte of Comparative Example 2 will still damage the reversibility of the battery. For the Zn||Cu battery assembled with the electrolyte of Example 1, due to the inhibition of hydrogen evolution, dendrites, and side reactions, the plating / stripping times of the battery are significantly extended, and the average coulombic efficiency after 1500 cycles is as high as 99.1%, proving that the battery has good reversibility at room temperature. At low temperatures, the average coulombic efficiency of the battery assembled using the electrolyte of Example 1 is still as high as 99.6% after 7000 cycles.
[0078] Test Example 11
[0079] The electrolytes prepared in Comparative Example 1 and Example 1 were assembled into Zn||NVO full cells for long cycle performance testing. The results are shown in Fig.13 and 14 shown.
[0080] First, the zinc foil was cut into discs with a diameter of 12 mm using a cutting machine. The cut zinc sheets were placed in a prepared phosphoric acid solution with a concentration of 0.1 mol / L to remove the zinc oxide layer on the surface. The zinc sheets were taken out after 30 seconds and ultrasonically cleaned three times with ethanol and deionized water alternately for two minutes each time. The sheets were then vacuum dried at 60°C for 2 hours and cooled to obtain the treated zinc sheet negative electrode.
[0081] Secondly, prepare the NVO positive electrode. 1g of vanadium pentoxide powder was dissolved in 30mL of 2mol / L sodium chloride solution, stirred at 30°C for 96 hours, and the suspension was washed with deionized water several times, and freeze-dried for two days to obtain a black-red product sodium vanadate (NVO). Then the obtained NVO was evenly ground with a mortar, and the active material NVO, Ketjen black, and PVDF binder were mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to disperse the mixed slurry. After the positive electrode slurry was stirred at room temperature at a speed of 800rmp for 4 hours, the mixed slurry was evenly scraped on a titanium foil with a thickness of 10μm using a scraper with a gap of 100μm, and the coated positive electrode was placed in a vacuum oven at 60°C for 6 hours and cooled at room temperature to obtain the NVO positive electrode. The cooled positive electrode was cut into NVO pole pieces with a diameter of 12mm by a cutting machine for the assembly of the full battery.
[0082] Finally, the Zn||NVO full battery was assembled in the order of CR2032 negative electrode shell, zinc sheet (80μm thick), glass fiber separator (675μm thick), electrolyte, NVO positive electrode, stainless steel sheet, shrapnel, and CR2032 positive electrode shell, and the full battery was subjected to long cycle tests at room temperature and low temperature of -20°C using the Xinwei charge and discharge test system.
[0083] like Fig.13 As shown, compared with Comparative Example 1 at room temperature, the capacity retention rate of the electrolyte in Example 1 after 3000 cycles at a current density of 5 A / g is 82.7%. Fig.14 As shown, at a low temperature of -20°C, the full battery using the electrolyte of Example 1 as the electrolyte has a capacity retention rate of 82.1% after 2000 cycles at 0.5 A / g, which indicates that the full battery using the electrolyte of Example 1 has a higher cycle stability.
[0084] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a low-temperature zinc ion battery double eutectic electrolyte, characterized in that: The steps include: S1, mixing zinc salt, acetamide and water in proportion, heating and stirring, and mixing evenly to obtain a hydrated eutectic electrolyte; wherein the molar ratio of the zinc salt, acetamide and water is 1:(3-6):(2.5-26), and water serves as a hydrogen bond donor; S2. Mix dimethyl sulfoxide and the hydrated eutectic electrolyte, heat and stir, and after mixing evenly, obtain a low-temperature zinc ion battery double eutectic electrolyte; wherein the molar ratio of the dimethyl sulfoxide to the water in step S1 is (2.5-26):2, and dimethyl sulfoxide serves as a hydrogen bond acceptor.
2. The method for preparing a low-temperature zinc ion battery double eutectic electrolyte according to claim 1, characterized in that: The zinc salt in step S1 is one of zinc chloride, zinc perchlorate hexahydrate, zinc trifluoromethanesulfonate or zinc bistrifluoromethanesulfonyl imide.
3. The method for preparing a low-temperature zinc ion battery double eutectic electrolyte according to claim 1, characterized in that: The concentration of zinc salt in the low-temperature zinc ion battery double eutectic electrolyte in step S2 is 1 to 5 mol / L.
4. The method for preparing a low-temperature zinc ion battery double eutectic electrolyte according to claim 1, characterized in that: In step S1, the heating temperature is 70-80° C., the stirring speed is 300-400 rpm, and the mixing time is 2-3 hours.
5. The method for preparing a low-temperature zinc ion battery double eutectic electrolyte according to claim 1, characterized in that: In step S2, the heating temperature is 70-80° C., the stirring speed is 300-400 rpm, and the mixing time is 0.5-2 h.
6. A low-temperature zinc ion battery double eutectic electrolyte, characterized in that: The low-temperature zinc ion battery double eutectic electrolyte is prepared by the preparation method of the low-temperature zinc ion battery double eutectic electrolyte as described in any one of claims 1 to 5.
7. An application of the low-temperature zinc ion battery double eutectic electrolyte as claimed in claim 6, characterized in that: The low-temperature zinc ion battery double eutectic electrolyte is used as an electrolyte in a zinc ion battery.
8. The use of a low-temperature zinc ion battery double eutectic electrolyte as claimed in claim 7, characterized in that: The zinc ion battery uses sodium vanadate as a positive electrode, a zinc sheet as a negative electrode, glass fiber as a diaphragm and a low-temperature zinc ion battery double eutectic electrolyte as an electrolyte.
9. The use of a low-temperature zinc ion battery double eutectic electrolyte as claimed in claim 8, characterized in that: The negative electrode, separator, electrolyte, positive electrode, stainless steel sheet and shrapnel are sequentially encapsulated into the battery shell. The encapsulation pressure is 50-80MPa, and the addition amount of the low-temperature zinc-ion battery double eutectic electrolyte is 140-180μL.
Citation Information
Patent Citations
Eutectic solvent electrolyte solution, preparation method thereof and aluminum ion secondary battery
CN114784384A
Aqueous zinc ion battery electrolyte and preparation method and application thereof
CN114976295A
Zinc ion battery electrolyte and preparation method and application thereof
CN117438670A
Apparatus for measuring thickness and collecting battery gas of bettery cell
KR102654390B1
Cited By
High-temperature-resistant anhydrous eutectic electrolyte for zinc ion battery as well as preparation method and application of high-temperature-resistant anhydrous eutectic electrolyte
CN121097213A
